Perancangan Bahan Ajar Digital Tema Gaya Hidup Berkelanjutan Terintegrasi Etno-PjBL untuk Pembelajaran Kurikulum Merdeka - Hermalina Daulay; Asrizal Asrizal (Postgraduate, University of Mataram, 2024)
This study aims to produce digital teaching materials on the theme of sustainable lifestyle integrated with Ethno-PjBL that are valid, practical, and effective for independent curriculum learning. The type of research used is design research with the Plomp model, which consists of a preliminary research stage, a prototype stage, and an assessment stage. The research is limited only to the practicality stage at the assessment stage, with a trial on 36 students of SMAN Kota Jambi in 2023/2024. The research instruments include teacher interview guidelines, needs analysis questionnaires, knowledge tests, creative thinking tests, validation instruments, and practicality. The data analysis technique used is descriptive analysis, namely describing the validity of Aiken's V and its practicality. The results of the study show that the digital teaching materials on the Theme of Sustainable Lifestyle Integrated with Ethno-PjBL for Independent Curriculum Learning have valid criteria and a very good level of practicality, according to teachers and students. Thus, this digital teaching material is valid and practical for use in learning